Uso del PCR como diagnóstico de Hemoplasmas en Encarnación y Asunción (Journal on studies and research of academic knowledge, 2014)
The aim of this study was the Hemotropic Mycoplasma detection by Polimerase chain reaction technique in domestic cats of Encarnacion and Asuncion cities. DNA was extracted from 42 blood samples (66,66%) then, 28 samples using GAPDH as a housekeeping gene were positive. For Mycoplasma haemominutum 2 samples (4,76%) were amplified, demonstrating the presence of this strain in the analyzed population.
Keywords: Hemotropic; Mycoplasma; PCR; bacterium; Feline